2022
DOI: 10.1007/s11684-021-0915-9
|View full text |Cite
|
Sign up to set email alerts
|

PathogenTrack and Yeskit: tools for identifying intracellular pathogens from single-cell RNA-sequencing datasets as illustrated by application to COVID-19

Abstract: Pathogenic microbes can induce cellular dysfunction, immune response, and cause infectious disease and other diseases including cancers. However, the cellular distributions of pathogens and their impact on host cells remain rarely explored due to the limited methods. Taking advantage of single-cell RNA-sequencing (scRNA-seq) analysis, we can assess the transcriptomic features at the single-cell level. Still, the tools used to interpret pathogens (such as viruses, bacteria, and fungi) at the single-cell level r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…We also tested Vulture local command line tools against Venus and PathogenTrack [15], [16] using three COVID-19 scRNA-seq run with different file sizes: a 1GB small sample (SRR12570205) from Bost et al [14], a 67 GB medium sample (SRR11537951) and a 141 GB large sample (SRR11181956) from Liao et al [35]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also tested Vulture local command line tools against Venus and PathogenTrack [15], [16] using three COVID-19 scRNA-seq run with different file sizes: a 1GB small sample (SRR12570205) from Bost et al [14], a 67 GB medium sample (SRR11537951) and a 141 GB large sample (SRR11181956) from Liao et al [35]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Viral-Track [14] is an existing computational pipeline that detects viral-host interactions in droplet scRNA-seq data by scanning host-unmapped reads for the presence of viral RNA. Based on a similar schema, Zhang et al and Lee et al developed PathogenTrack [15] and Venus [16] which have added capabilities. PathogenTrack can quantify bacteria in addition to viruses; the tool was benchmarked to be mostly correlated in microbial unique molecular identifiers (UMIs) called as and faster in run time than Viral-Track [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dataset integration was performed by Seurat software (14) in R, using the Harmony method (15) for integrating different batches of samples. Then, data were visualized using the Yeskit tool (16). The transcriptome data on The Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA-LIHC) were processed using the Cell-type Identification be Estimating Relative Subsets of RNA Transcripts (CIBERSORT) tool (17) for calculating each proportion of immune cell subtype.…”
Section: Hcc Single-cell Transcriptome Datasetmentioning
confidence: 99%
“…Wei Zhang’s team developed an algorithm called PathogenTrack that is based on unsupervised identification of features of the intracellular microbiota extracted from scRNA-seq data. Using this algorithm, they found that a small percentage of cells in the bronchoalveolar lavage fluid (BALF) samples of a COVID-19 patient, including neutrophils and macrophages, were infected with Haemophilus parahemolyticus [ 67 ], a bacterium that is usually associated with ARDS and septic shock [ 68 ].…”
Section: Recognition Of Pathogen–cell Interactionsmentioning
confidence: 99%